GENDER EQUALITY-BASED ECONOMIC GROWTH IN SOUTHERN KALIMANTAN PROVINCE - Farid, Fuad Muhajirin; Rahkmawati, Yeni; Hafizi, Muhammad Riza; Fidiyaningsih, Yani; Salsabila, Nur; Sidauruk, Verina Rosalin Br (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Gender equality is one of the issues of several Sustainable Development Goals (SDGs), in the economic development sector is one of the targets in sustainable development. Gender equality is the condition of providing opportunities for women and men to be equal / comparable in enjoying rights as individuals, socially with the opportunity to own objects, opportunities, resources and enjoy the benefits of development results. The purpose of this study is to identify the influence of gender roles on economic growth in South Kalimantan Province, and determine the recommendations given as a basis for policies to increase economic growth based on gender equality in South Kalimantan Province. The method used in analyzing is panel data regression modeling. The results of this study concluded that based on the results of the Chow and Hausman tests, the Fixed Effect Model (FEM) is the right model to use in modeling gender equality-based economic growth in South Kalimantan Province with an R-Squared value of 0.5722, with the intention of being able to identify economic growth in South Kalimantan Province by 57.22% based on gender equality. Keyword: Gender Equality, Economic Growth, and Panel Data Regression